Energy Balances and Greenhouse Gas Emissions of Bagasse-based Electricity Production in Kenya - Mwanyasi, Fridah; Mbothu, Joseph; Kamrudin Bachani, Sameer; Kidegho, Gideon (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Biofuels have been advocated in many nations to solve environmental issues, energy security, and the socio-economic well-being of rural residents. This study assessed energy consumption, energy balances, and lifetime net greenhouse gas emissions in Kenya's bagasse-based electricity generating chain. Production of electricity from bagasse involves the cultivation of sugarcane, milling the cane, and cogeneration. By conducting a Life Cycle Assessment, the study used the economic allocation model to partition energy inputs and their respective greenhouse gas emissions. The life cycle greenhouse gas emissions were estimated to be 24.53 kgCO2eq/MWh of electricity generated, while the total energy consumption from both renewable and non-renewable energy sources inputs was evaluated as 181.26 MJ/MWh. The information from the energy balances computed per MWh of electricity revealed a net energy value (NEV) of 9,349 MJ, a net renewable energy value (NREV) of 9,387 MJ and a net energy ratio (NER) of 84. The high positive values of NREV and NER are indicators that minimal amount of fossil fuel is required to produce 1 MWh of electricity. Bagasse-based cogeneration offers great promise for application in electricity production in Kenya, as can be deduced from the results presented here.
Keywords: Energy balances, Life cycle assessment, Sugarcane bagasse, Greenhouse gases, Kenya